Penerapan Konsep Behaviorisme Dalam Pendidikan Islam - Aji, Wahyu; S, Ramlah; S, Saprin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The role of educators is crucial in designing learning, choosing the right theories, strategies, and methods to make teaching more effective. Every teacher also has a different approach in choosing the theories they use. Behaviourism learning theory can be used to help the learning process so it needs to be further studied by delving into behaviourism learning theory according to the experts, the models of behaviorism learning theory and the perspective of Islamic education towards behaviorism learning theory. This study is a literature study using sources from written references. The result of this research is learning behaviorism according to the experts is a view that emphasizes that learning is a change in behavior that can be directly observed. The learning theory models of behaviorism emphasize that learning occurs through associations between stimuli and directly observable responses. Behaviorism Learning Theory in Islamic Educational Perspective is that it emphasizes on the formation of behavior through stimulus and response. In Islamic education, this approach can be integrated with Islamic teachings that prioritize the formation of morals and positive behavior through habituation (ta’dib), example, and repetition.